2023
DOI: 10.1021/acs.orglett.3c01168
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Ketonitriles via N-Heterocyclic-Carbene-Catalyzed Radical Coupling of Aldehydes and Azobis(isobutyronitrile)

Abstract: Herein, an NHC (N-heterocyclic carbene)-catalyzed radical coupling reaction between aldehydes and azobis-(isobutyronitrile) (AIBN) has been developed. This method provides an efficient and convenient approach for the synthesis of β-ketonitriles containing a quaternary carbon center (31 examples, up to >99% yield) utilizing commercially available substrates. This protocol features broad substrate scope, good functional group tolerance, and high efficiency under metal-free and mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 72 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…N -Heterocyclic carbenes (NHCs), as a kind of biomimetic organocatalysts, have played an increasingly important role in organic synthesis in recent decades . However, the majority of NHC-involved transformations, in large part, relied on substrates that possess an active carbonyl functional group (such as aldehydes, ketenes, and acyl fluorides) . Recently, Wang’s group reported a series of NHC-catalyzed aldehyde-free mechanistic routes to access the highly functionalized N-heterocycles .…”
Section: Introductionmentioning
confidence: 99%
“…N -Heterocyclic carbenes (NHCs), as a kind of biomimetic organocatalysts, have played an increasingly important role in organic synthesis in recent decades . However, the majority of NHC-involved transformations, in large part, relied on substrates that possess an active carbonyl functional group (such as aldehydes, ketenes, and acyl fluorides) . Recently, Wang’s group reported a series of NHC-catalyzed aldehyde-free mechanistic routes to access the highly functionalized N-heterocycles .…”
Section: Introductionmentioning
confidence: 99%
“…The process requires only heating a solution of 1 , and the temperature can be adjusted to control the half-life. For instance, several reports have demonstrated that azobis­(alkylcarbonitirles) 1 are suitable radical precursors for functionalizing π-systems such as alkenes, alkynes, isocyanides, and aldehydes . Efforts have also been made toward the group-directed C­(sp 2 )–H alkylation using azo initiators. Notably, to the best of our knowledge, the direct C­(sp 2 )–H functionalization of heteroarenes using azobis­(alkylcarbonitriles) 1 (Figure c) has not been explored.…”
mentioning
confidence: 99%
“…−2 V vs SCE). Very recently, primary and secondary unactivated alkyl iodides and bromides ( E red < −2 V) have been acylated via NHC organocatalysis. , Note that in the case of these substrates, an SN 2 reaction with Breslow intermediates is also possible, and it is likely that both ionic and radical pathways coexist. In any case, tertiary alkyl halides remain out of reach and therefore represent the new redox frontier for NHC-catalyzed radical activation of electrophiles. …”
mentioning
confidence: 99%
“…We chose thiazol-2-ylidene NHC1 , an efficient organocatalyst for a plethora of radical NHC-catalyzed transformations of aldehydes. , Indeed, we showed that it yields Breslow-type enolates with oxidation potentials ca. −1.4 V vs SCE, a largely sufficient value for the reduction of the targeted Ni I complex at E Ni(0)/Ni(I) = −0.9 V. Thus, optimized reaction conditions for the coupling between 4-chlorobenzaldehyde ( 1a ) and t BuI ( 2a ) leading to 3aa in 78% NMR yield were found employing 25 mol % of thiazol-2-ylidene precursor NHC1 -HPF 6 , 5 mol % of the in situ generated nickel Xantphos complex, and 1,8-diazabicyclo[5.4.0]­undec-7-ene (DBU) as the base in THF at 45 °C (Table , entry 1).…”
mentioning
confidence: 99%